Tinjauan Yuridis tentang Peran Notaris dalam Penyusunan Akta Jual Beli Tanah di Indonesia - Mahar, Revintalis Osilia (UM Purwokerto Press, 2024)
The aim of this research is to look from a juridical perspective on the role of Notaries in making land sale and purchase deeds in Indonesia. The background to this problem is that the land sale and purchase deed is very important as proof of the validity of the transaction and the existence of legal certainty in the land sale and purchase process. The research method used is normative juridical, namely reviewing related laws and regulations and reviewing legal literature and documents. Research shows that notaries play an important role in ensuring the validity of land sale and purchase deeds. The notary is tasked with checking the validity of supporting documents, ensuring that transactions are carried out voluntarily and without coercion, as well as recording and storing deeds for future use. This research found that the presence of a Notary plays an important role in the process of making a sale and purchase deed.